Influence of electrolytes and hydroxypropylsulfonation on paste stability of cassava starch/polyvinyl alcohol blend sizes for warp sizing. (January 2020) - Li, Wei; Wu, Lanjuan; Zhang, Zhengqiao; Lu, Yuhao
The aim of this research was to ascertain the influences of electrolytes and hydroxypropylsulfonation on paste stabilities of cassava starch/polyvinyl alcohol blend sizes. The hydroxypropylsulfonated cassava starch was prepared via hydroxypropylsulfonation of hydrolyzed cassava starch with 3-chloro-2-hydroxypropyl sulfonic acid sodium in an aqueous medium. The stability was evaluated by measuring the initial demixing time. Before and after the addition of the electrolytes such as NaH2 PO4, Na2 SO4, and NaCl, the initial demixing time was 24, 20, 18, and 15 min for hydroxypropylsulfonated cassava starch/PVA1799 paste and 21, 17, 15, and 14 min for hydrolyzed cassava starch/PVA1799 one. This showed that the electrolytes accelerated the separation rates of hydroxypropylsulfonated cassava starch/polyvinyl alcohol blend pastes and hydrolyzed cassava starch/polyvinyl alcohol ones, thereby reducing the stability, and the acceleration followed the order: NaH2 PO4  > Na2 SO4  > NaCl. Increasing the concentration of electrolyte accelerated the separation rate and lowered the stability. The hydroxypropylsulfonation was able to reduce the separation rate and enhance paste stability. When the weight percentage of starch was fixed, with the rise in the degree of substitution from 0.011 to 0.029, the initial demixing time gradually increased, indicating the gradual decreases in the separation rates, thereby promoting the enhancement in the stability. Moreover, PVA0588 was lower than PVA1799 and PVA1788 in affecting the separation rate, which implied that polyvinyl alcohol with a lower degree of polymerization favored to promote the stability.